Public Perspective Towards Illegal Renovation Dilemma among Landed Residential in Kuala Lumpur - Zan, Rubiah Md; Manteghi, Golnoosh; Mohayat, Sarimah; Azmi, Nurdiana; Senawi, Asma (International Journal of Psychosocial Rehabilitation, 2020)
In Kuala Lumpur renovation has become a popular trend for house owner to carry out this activity even before they move into the house. This is happening as most landed housing in Kuala Lumpur were designed in monotonous and repetitive arrangement which triggered house owner to renovate to make it personal to suit their taste and need. Renovation activities in Malaysia especially if it involves structure and façade are required to get LA approval and there are rules and procedure that the owner need to adhere. In view of this situation LA received many complaints on the illegal renovation. This has given bad reputation to the LA as their function is to ensure the protection of public interest and as well as safety within their authorized boundary. This research is focusing on public perspective on illegal renovation within Kuala Lumpur vicinity and the objective of this study is to identify public awareness and knowledge on this issue. Most cases of illegal residential renovation reported within the area of elite community such as in Central Regional Zone 2. Among the factors that caused this situation are due to owners are framed or scammed by contractor and not aware on the procedure.